Post-neoadjuvant treatment with capecitabine and trastuzumab emtansine in breast cancer patients—sequentially, or better simultaneously? - Piroth, Marc D.; Krug, David; Sedlmayer, Felix; Duma, Marciana Nona; Baumann, René; Budach, Wilfried; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: Following neoadjuvant chemotherapy for breast cancer, postoperative systemic therapy, also called post-neoadjuvant treatment, has been established in defined risk settings. We reviewed the evidence for sequencing of postoperative radiation and chemotherapy, with a focus on a capecitabine and trastuzumab emtansine (T-DM1)-based regimen. Methods: A systematic literature search using the PubMed/MEDLINE/Web of Science database was performed. We included prospective and retrospective reports published since 2015 and provided clinical data on toxicity and effectiveness. Results: Six studies were included, five of which investigated capecitabine-containing regimens. Of these, four were prospective investigations and one a retrospective matched comparative analysis. One randomized prospective trial was found for T‑DM1 and radiotherapy. In the majority of these reports, radiation-associated toxicities were not specifically addressed. Conclusion: Regarding oncologic outcome, the influence of sequencing radiation therapy with maintenance capecitabine chemotherapy in the post-neoadjuvant setting is unclear. Synchronous administration of capecitabine is feasible, but reports on possible excess toxicities are partially conflicting. Dose reduction of capecitabine should be considered, especially if normofractionated radiotherapy is used. In terms of tolerance, hypofractionated schedules seem to be superior in terms of toxicity in concurrent settings. T‑DM1 can safely be administered concurrently with radiotherapy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Breast cancer; Capecitabine; Radiochemotherapy; Radiotherapy; T‑DM1